Pengaruh Kualitas Pelayanan dan Lokasi Terhadap Loyalitas Konsumen dengan Kepuasan Konsumen sebagai Variabel Intervening - Shella Monica; Tinton Ramadhan (KALBISIANA Jurnal Sains, Bisnis dan Teknologi, 2022)
This study aims to determine how much influence service quality and location have on customer loyalty with customer satisfaction as an intervening variable in bakmie akim. This research is a quantitative research with a total sample of 120 respondents who have bought bakmie akim in the first and second branches using purposive sampling technique. The results of this study indicate that service quality and location influence customer satisfaction, service quality and location affect customer loyalty, and customer satisfaction affects customer loyalty.